Algoritmo numérico para projeto de sistemas hidráulicos - Couto, Nilton Castro (1978)
This work aims at the development of a algorithm within the Fluids Mechanical area to the computational installations and hydraulic systems design. It mainly consists of the development of a method of hydraulic systems design compatible to the use of computational methods connected with the design variation and with the incompressible fluids' move characteristics and Newtonian one, in a stationary mood. Held to such purpose, a numerical algorithm was developed through the use of equations from Darcy – Weisbach Hazen Poiseuille and Hazen-Williams, to figure out the loss of charge, and from Colebrook, to figure out the factor of friction. Colebrook's equation solution was gotten by the use of iterative method. The characteristics to establish Newton-Raphson's coefficients of resistence within the hydraulic systems elements, such as valves, reductions, derivations and so one, compose a second algorithm to the secondary lasses of charge. This numerical algorithm corresponds to a convergent iterativa system and fits on several loops and on patterns of the systems design. The whole schedule, composed of usual calculation, also makes use of a small iterative scheme for correcting the increments of drainages in each system loop, while, at the sarne time, it controls the necessary changes which come from the use of the secondary elements. The secondary elements are calculated according to the conventional equations from the existing literature, in a cinetic energy mood, so that to facilitate the inclusion of further details whenever they are necessary. Besides, the schedule is okay for restrictive specifications in pressure of ejection on different points of the loops' intersuction and for this reason the schedule makes possible a quick study on the system's behavior acting by putting in order, automatically, the diameter of tubes.